The Infection of Vibrio parahaemolyticus in Shrimp and Human - Rian Ka Praja; Dwi Putri Safnurbaiti (Oceana Biomedicina Journal, 2018)
Vibrio parahaemolyticus is an aquatic zoonotic agent that can threaten human and aquaculture animal health. Humans can be infected by consuming contaminated raw seafood or wound-related infections. Generally infection of V. parahemolyticus is orally transmitted and causes gastroenteritis in humans while in aquaculture animals especially shrimp can cause Acute Hepatopancreatic Necrosis Disease (AHPND) or Early Mortality Syndrome (EMS) with a very high mortality rate and cause economic losses. Shrimp species susceptible to infection are Litopenaeus vannamei, Penaeus monodon, and P. chinensis. V. parahaemolyticus produces several toxins in human disease such as thermostable direct hemolysin (TDH), TDH-related haemolysin (TRH), and thermolabile hemolysin (TLH). Meanwhile, Photorabdus insect-related (Pir) toxins consisting of PirAvp and PirBvp are the toxins associated with AHPND in shrimp. The genes that encode the toxin are used as targets to diagnose V. parahaemolyticuspathogens molecularly. Until now the treatment of V. parahaemolyticus infection is using antibiotics and fluid therapy, but there were V. parahaemolyticus isolates from aquaculture that have been resistant to antibiotics so that the use of antibiotics in aquaculture must be controlled and the use of alternative therapy are very important to be developed to control V. parahaemolyticus infection.